Additive effect of EPO and altitude on hemoglobin mass but not peak oxygen uptake - Bonne, T. C.; Breenfeldt Andersen, A.; Bejder, J.; Loures, J. P.; Dam, C.; Huertas, J. R.; Nordsborg, N. B. (Medicine & Science in Sports & Exercise, 2025)
Purpose This study evaluated whether recombinant human erythropoietin (rhEpo) treatment combined with hypoxia provided an additive effect on hemoglobin mass (Hbmass) and peak oxygen uptake (VO2peak) compared with altitude or rhEpo alone.